2012
DOI: 10.1111/j.1742-7843.2012.00880.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in the in vivo DMBA Rat Model of Breast Cancer: Suppression by a Voltage‐gated Sodium Channel Inhibitor (RS100642)

Abstract: Breast cancer (BCa) was induced in vivo in female rats with 7,12-dimethylbenz(a)anthracene (DMBA). Two main questions were addressed. Firstly, would the carcinogenesis be accompanied by oxidative stress as signalled by superoxide dismutase, glutathione peroxidase, malondialdehyde and total nitrate? Secondly, would treating the rats additionally with a blocker of voltage-gated sodium channel (VGSC) activity, shown previously to promote BCa progression, affect the oxidative responses? The DMBA-induced increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 47 publications
4
34
0
Order By: Relevance
“…Therefore, targeting oxidative stress proposes potential new therapeutic approaches . Consistent with previous studies , we observed an overt oxidative stress status in mice of D1 group demonstrated as increased MDA and TOS in tumor tissue. Administration of simvastatin especially at its higher dose as well as tamoxifen decreased the severity of oxidative stress.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, targeting oxidative stress proposes potential new therapeutic approaches . Consistent with previous studies , we observed an overt oxidative stress status in mice of D1 group demonstrated as increased MDA and TOS in tumor tissue. Administration of simvastatin especially at its higher dose as well as tamoxifen decreased the severity of oxidative stress.…”
Section: Discussionsupporting
confidence: 91%
“…Batcioglu et al 61 showed the importance of VGSCs inhibition in a rat model of induced breast cancer in order to inhibit antioxidant response. They observed a survival improvement in rats treated with a VGSC blocker.…”
Section: Voltage-gated Sodium Channelsmentioning
confidence: 99%
“…There are three major ER-positive cell lines commonly used, such as MCF-7 [66], T47D [67], and ZR-75-1[68]. In addition, overexpression of genes involved in breast cancer and mutagenesis induced by the mouse mammary tumor virus (MMTV) or polyoma middle-T antigen (PyMT) [69], or treatment with chemical agents, such as 7,12-dimethylbenz(a)anthracene (DMBA) [70], medroxyprogesterone acetate (MPA) [71], or N-methyl-N-nitrosourea (NMU) [72], can induce ER-positive mammary tumors in experimental animals. Furthermore, estrogen-mediated mammary carcinogenesis models are based on long-term subcutaneous administration of estrogen using slow-release pellets or silastic tubes [73].…”
Section: Natural Products Against Er-positive Breast Cancermentioning
confidence: 99%